Kebebasan Beragama sebagai Hak Minoritas Menurut Multikulturalisme Will Kymlicka (Pengalaman Gereja Stasi St. Yosep Maluk): Freedom of Religion as a Minority Right According to Will Kymlicka's Multiculturalism (Experience of the St. Joseph Maluk Church) - Radja, Nikolaus Tabe (Undiksha, 2025)
The focus of this study is to elaborate and criticize the church life of St. Yosep Maluk Church in fighting for its faith. The effort of the people in fighting for faith in Christ is a challenging journey. The presence of the Gold Mining Industry there since 30 years ago invited many people to come to work, including those who were Catholic. The church was first formed because the miners longed for spiritual nourishment through the Eucharist. However, their efforts to fight for their rights as religious people have encountered obstacles because until now they do not have a church to worship. Church life at St. Yosep Maluk Church is a form of minority rights that must be guaranteed by the state and society. The purpose of this study is to analyze the presence of people in St. Yosep Maluk Church as a minority that must be considered in the system of living together. The methodology used in this study is an interpretative methodology by conducting depth interviews and studying related literature. The findings of this study are that minority groups are first recognized and their rights are protected in order to create a tolerant and multicultural society.